2005
DOI: 10.1242/jeb.01440
|View full text |Cite
|
Sign up to set email alerts
|

Hypotonicity induced K+ and anion conductive pathways activation in eel intestinal epithelium

Abstract: The electrophysiological response to hypotonic stress was completely abolished by Ca 2+ removal from the Ringer perfusing solution, but was not affected by depletion of intracellular Ca 2+ stores by thapsigargin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 66 publications
(65 reference statements)
3
33
0
Order By: Relevance
“…As previously demonstrated [44] the eel intestinal epithelium responded to a hypotonic challenge with a Ca 2+ -dependent biphasic decrease in V te and Isc (Fig. 6, control trace) which is correlated with a regulatory volume decrease (RVD) response.…”
Section: Role Of Bk Channels In Rvdsupporting
confidence: 72%
See 2 more Smart Citations
“…As previously demonstrated [44] the eel intestinal epithelium responded to a hypotonic challenge with a Ca 2+ -dependent biphasic decrease in V te and Isc (Fig. 6, control trace) which is correlated with a regulatory volume decrease (RVD) response.…”
Section: Role Of Bk Channels In Rvdsupporting
confidence: 72%
“…As previously demonstrated [42,43] this epithelium is sensitive to the osmolarity of the extracellular medium and shows a dynamic regulation of cell volume with a RVD response after hypotonic stress, making this tissue a good physiological model for epithelial cell volume regulation research. As previously demonstrated by short circuit current measurements [44] hypotonicity induces a Ca 2+ -dependent biphasic decrease of V te and Isc, that was attributed to the hypotonicity induced activation of several ion channels including iberiotoxin-sensitive K + channels [44]. In the present paper using rat BK channel-specific primer, a RT-PCR signal of 696 pb cDNA was detected in eel intestine, whole nucleotide sequence showed high similarity (83%) to the alpha subunit of BK channel fam- ily.…”
Section: +supporting
confidence: 60%
See 1 more Smart Citation
“…The Na ϩ -K ϩ -ATPase on the basolateral membrane provides the driving force for NKCC2, a model similar to that proposed for the mammalian cTAL. It has been shown that swelling-activated K ϩ and anion-conductive pathways are important in the response to hypotonicity in the eel intestine (572), and that conversely, shrinkage activation of NKCC2 plays a central role in the response to hypertonicity (573; see Refs. 368, 575; see also sect.…”
Section: Osmotic Regulation Of Salt Transportmentioning
confidence: 99%
“…The cell volume regulation mechanisms are highly conserved and principally similar in cells from various tissues as well as between evolutionary distant species [22,23,24,25,26,27]. Following a hypotonic cell swelling, they consist in the release of osmolytes, mainly K + and Cl - , followed by loss of osmotically obliged water and are termed Regulatory Volume Decrease (RVD); following a hypertonic shrinkage they consist in the uptake of osmolytes followed by gain of osmotically obliged water and are termed Regulatory Volume Increase (RVI) [28,27].…”
Section: Introductionmentioning
confidence: 99%